Relasi Antar Disiplin Ilmu: Paradigma Integrasi dan Interkoneksi (Transdisiplinaritas) Ilmu Pengetahuan dengan Pendidikan Islam - Marzuki, Marzuki; Ghifari, Ahmad; Dirman, Dirman (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2023)
This study discusses the importance of integrating and interconnecting various disciplines in education, particularly through a transdisciplinary approach in the context of Islamic education, termed "Islamic transdisciplinary approach." This approach, which is comprehensive, multidimensional, and holistic, aids in integrating various disciplines with Islamic education. The purpose of this article is to explore the role of knowledge in Islam and how science is integrated and interconnected with Islam. The research methodology is qualitative, utilizing literature analysis, with books, articles, and journals as sources. The findings indicate that in Islam, knowledge serves both as a tool and a medium.